Roles of extracellular vesicles derived from healthy and obese adipose tissue in inter-organ crosstalk and potential clinical implication - Han, Yue; Ye, Sheng; Liu, Bowen (Frontiers in Endocrinology, 2024)
Extracellular vesicles (EV) are nanovesicles containing bioactive molecules including proteins, nucleic acids and lipids that mediate intercellular and inter-organ communications, holding promise as potential therapeutics for multiple diseases. Adipose tissue (AT) serves as a dynamically distributed energy storage organ throughout the body, whose accumulation lead to obesity, a condition characterized by infiltration with abundant immune cells. Emerging evidence has illustrated that EVs secreted by AT are the novel class of adipokines that regulate the homeostasis between AT and peripheral organs. However, most of the studies focused on the investigations of EVs derived from adipocytes or adipose-derived stem cells (ADSC), the summarization of functions in cellular and inter-organ crosstalk of EVs directly derived from adipose tissue (AT-EV) are still limited. Here, we provide a systemic summary on the key components and functions of EVs derived from healthy adipose tissue, showing their significance on the tissue recovery and metabolic homeostasis regulation. Also, we discuss the harmful influences of EVs derived from obese adipose tissue on the distal organs. Furthermore, we elucidate the potential applications and constraints of EV from healthy patients lipoaspirates as therapeutic agents, highlighting the potential of AT-EVs as a valuable biological material with broad prospects for future clinical use.